A Study of Hybridization Between Marmota baibacina and M. sibirica in Their Secondary Contact Zone in Mongolian Altai - Brandler, Oleg V.; Kapustina, Svetlana Yu.; Nikol’skii, Alexander A.; Kolesnikov, Viacheslav V.; Badmaev, Bair B.; Adiya, Yansanjav (Frontiers in Ecology and Evolution, 2021)
The role of hybridization as one of the factors of speciation in mammals has been underestimated for a long time, but now there is a lot of data on its impact in mammalian evolution. Hybridization of species often occurs in their secondary contact zones, which is a natural model for testing factors that ensure species integrity. Studies of hybrid zones are increasingly revealing the essential role of ecological and behavioral features both in initiating crossbreeding and in maintaining interspecific barriers. We studied the hybridization of two species of marmots Marmota baibacina and M. sibirica in the zone of sympatry in Mongolian Altai Mountains. We used a bioacoustic approach to determine the localization of individuals of different species and their cohabitation sites. Genetic typing with two diploid nuclear markers and one marker each of paternal and maternal lines was used to identify hybrids. Habitat preferences of marmots were studied to understand the conditions for the formation of heterospecific pairs. We found a high proportion of hybrid individuals in boulder screes where conditions for the formation of heterospecific pairs probably exist. Our data indicate the viability and fertility of F1 hybrids and their descendants. We hypothesize that the environmental preferences and behavioral features of both species of marmots are important factors that both create conditions for hybridization and limit hybrid dispersal.